MOTIVATION FOR CHANGE IN ALCOHOL CONSUMPTION: BRIEF INTERVENTION AS A MOTIVATIONAL STRATEGY - Lima, Nicole Teixeira Xavier; Lopes, Milena Riêra; Souza, Maria José Silva; Reis, Ilka Afonso; Reinaldo, Amanda Márcia dos Santos; Rabelo, Juliana Lemos; Soares, Janaína (Cogitare Enfermagem, 2022)
Objective: to analyze the effect of brief intervention on motivation to change alcohol consumption. Method: experimental, follow-up study, conducted with 43 participants in two Basic Health Units. The Alcohol Use Disorders Identification Test, the Change Readiness Ruler, and a socioeconomic questionnaire were applied. Results: The experimental group showed a median equal to 10 points (maintenance stage) at the beginning and after 30 days. In the segment, the median was equal to eight points (action stage). The control group had a median equal to eight points at the beginning and after 30 days (action stage). In the segment, median equal to seven points (planning stage). In the 30-day intermediate evaluation, it was noted that there was a statistical difference in motivation between the two groups (p=0.029). Conclusion: it was concluded that the Brief Intervention was effective in maintaining motivation in the stages of action and maintenance of change in the consumption of alcoholic drinks.